Effect of oxidation on intrinsic residual stress in amorphous silicon carbide films. Issue 5 (15th October 2018) - Deku, Felix; Mohammed, Shakil; Joshi‐Imre, Alexandra; Maeng, Jimin; Danda, Vindhya; Gardner, Timothy J.; Cogan, Stuart F.
Abstract: The change in residual stress in plasma enhanced chemical vapor deposition amorphous silicon carbide (a‐SiC:H) films exposed to air and wet ambient environments is investigated. A close relationship between stress change and deposition condition is identified from mechanical and chemical characterization of a‐SiC:H films. Evidence of amorphous silicon carbide films reacting with oxygen and water vapor in the ambient environment are presented. The effect of deposition parameters on oxidation and stress variation in a‐SiC:H film is studied. It is found that the films deposited at low temperature or power are susceptible to oxidation and undergo a notable increase in compressive stress over time. Furthermore, the films deposited at sufficiently high temperature (≥325 C) and power density (≥0.2 W cm −2 ) do not exhibit pronounced oxidation or temporal stress variation. These results serve as the basis for developing amorphous silicon carbide based dielectric encapsulation for implantable medical devices. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1654–1661, 2019.